IMPROVING THE COOPERATION OF PRESCHOOL AND PRIMARY EDUCATION PEDAGOGUES IN THE PROCESS OF INCLUSIVE EDUCATION - Juraboyeva Mastura; Jalolova.M (TADQIQOTLAR, 2025)
Annotation:  This  work  focuses  on  improving  the  cooperation  between preschool  and  primary  education  pedagogues  within  the  framework  of  inclusive education.  The  study  emphasizes  the  importance  of  continuity  in  pedagogical approaches, mutual understanding of developmental needs, and coordinated support strategies for children with special educational needs. It explores methods of fostering professional collaboration, joint planning, and communication between educators to ensure a smooth transition and consistent support for learners. The outcomes aim to contribute to more effective inclusive practices and a unified educational environment.